Madura Island Halal Tourism Potential: A Sustainable Coastal Tourism Approach - Dedeng Permadi; Nasrulloh Nasrulloh (University of Darussalam Gontor, 2023)
Pamekasan Regency has various kinds of tourism potential, especially coastal tourism. One of the coastal tourism areas that has the potential to be developed is Jumiang Beach. The beach has various potentials including a strategic location, easy access, exotic natural scenery, and cultural activities that are regularly held. This study aims to provide an overview of the development strategy used by all parties involved in managing Jumiang Beach in Pademawu sub-district to become halal tourism through Sustainable Coastal Tourism and how Jumiang Beach Strategy becomes a leading halal tourism in terms of Sustainable Coastal Tourism approach. This study uses descriptive qualitative research methods. The data collection technique used by the researchers in this study was to conduct observations and interviews aimed at coastal tourism managers, the village, and the government. Researchers also use literature or literature studies that are in accordance with the object of research to support research. The results of this study indicate that the coastal tourism area in Pademawu District, Pamekasan Regency has various potentials like natural beauty, the facilities, and many others. On the other hand, there are still many things that need to be addressed in the tourist area, for example, such as inadequate facilities so development is needed through a concept that is in accordance with the conditions of the tourist area.